Pengaruh Intellectual Capital, Corporate Social Responsibility, Dan Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2021 - Reva Faturachman Soetrisno; M. Wahyullah; Elvina Setiawati (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This study aims to examine the effect of Intellectual Capital, Corporate Social Responsibility and Good Corporate Governance on the financial performance of manufacturing companies listed on the IDX for the 2018-2021 period. So that the research variables consist of 3 (four) independent variables, namely intellectual capital (X1), Corporate Social Responsibility (X2), Good Corporate Governance (X3) the dependent variable is Return on equity (Y). The population of this study are manufacturing companies listed on the Indonesia Stock Exchange during the 2018-2021 period. Samples were taken using purposive sampling. The type of data used in this research is quantitative data. The data analysis method used in this study is a method of multiple linear regression statistical analysis. The results of this study indicate that Intellectual Capital (X1) has an effect on Company Performance which is proxied by Return on Equity, Corporate Social Responsibility (X2) has no effect on Company Performance which is proxied by Return on Equity, Good Corporate Governance (X3) has an effect on Company Performance which is proxied by Return on Equity, and. The results of this study also show that the independent variables (Intellectual Capital, Corporate Social Responsibility, and Good Corporate Governance) are 72.3%. While the remaining 27.7% of the quality of financial performance is influenced by other variables.